Dexmedetomidine versus midazolam for sedation during endoscopy: A meta-analysis - ZHANG, FAN (Exp Ther Med, 2016)
Patients undergoing endoscopy frequently require sedation, which commonly includes the administration of midazolam or dexmedetomidine. Previous meta-analyses have mainly focused on comparing the effects of these two drugs in intensive care unit patients. In the present study, randomized controlled trials (RCTs) that compared the sedative and clinical effectiveness of these two drugs in patients undergoing endoscopy were searched in a number of databases. The meta-analysis showed that dexmedetomidine demonstrated a significantly lower rate of respiratory depression and adverse events compared with those presented upon midazolam administration. A significant difference was also observed in the sedation potency of the sedatives. The current controlled data suggest that dexmedetomidine may be an alternative to midazolam in the sedation for endoscopy. However, more high-quality and well-designed studies are required to further evaluate this conclusion.